Perlindungan Para Kreditor Sehubungan Dengan Debitor Mempailitkan Diri - Supriyono Supriyono (UIN Sunan Kalijaga Yogyakarta, 2013)
Debtors can file for bankruptcy if having two or more creditors who can not run the obligations to pay the debt and interest that was due. In this case the bankruptcy petition aimed at the Commercial Court and the Commercial Court should be granted if there is the fact that in accordance with the terms of the bankruptcy has been met by the party who filed for bankruptcy. For Debtors filed for bankruptcy itself the conditions are that the debtor has two or more creditors and not pay at least one debt that has matured. In this study the authors focused on the protection of creditors in connection with bankruptcy debtors themselves.